The Combination of Lime and Plant Species Effects on Trace Metals (Copper and Cadmium) in Soil Exchangeable Fractions and Runoff in the Red Soil Region of China - Xu, Lei; Xing, Xiangyu; Cui, Hongbiao; Zhou, Jing; Zhou, Jun; Peng, Jianbiao; Bai, Jingfeng; Zheng, Xuebo; Ji, Mingfei (Frontiers in Environmental Science, 2021)
Abstract：The water-soluble heavy metal ions in contaminated soil may enter aquatic ecosystem through runoff, thus causing negative impact on the water environment. In this study, a two-year in situ experiment was carried out to explore an effective way to reduce the runoff erosion and water-soluble copper (Cu) and cadmium (Cd) in a contaminated soil (Cu: 1148 mgkg-1, Cd: 1.31 mg kg-1) near a large Cu smelter. We evaluated the ability to influence soil properties by four Cu-tolerance plant species (Pennisetum sp., Elsholtzia splendens, Vetiveria zizanioides, Setaria pumila) grown in a contaminated acidic soil amended with lime. The results show that the addition of lime can significantly reduce the exchangeable fraction (EXC) of Cu and Cd in soil (81.1%-85.6% and 46.3%-55.9%, respectively). Plant species cannot change the fraction distributions of Cu and Cd in the lime-amended soils, but they can reduce the runoff generation by 8.39%-77.0%. Although water-soluble Cu concentrations in the runoff were not significantly differed and water-soluble Cd cannot be detected among the four plant species, the combine remediation can significantly reduce 35.9%-63.4% of Cu erosion to aquatic ecosystem, following the order: Pennisetum sp. > Elsholtzia splendens > Vetiveria zizanioides > Setaria pumila. The implication of this study would provide valuable insights for contaminated soil management and risk reduction in the Cu and Cd contaminated regions.